Comparative genome analysis of the Sphaerotilus-Leptothrix group supports the unification of the genera Sphaerotilus and Leptothrix into a single emended genus Sphaerotilus - Dmitry D. Smolyakov; Alexey V. Beletsky; Tatyana S. Rudenko; Maria V. Gureeva; Nikolai V. Ravin; Margarita Y. Grabovich (Systematic and Applied Microbiology, 2025)

Cross-scale prediction for the Laurentian Great Lakes - Y. Joseph Zhang; Joshua Anderson; Chin H. Wu; Dmitry Beletsky; Yuli Liu; Wei Huang; Eric J. Anderson; Saeed Moghimi; Edward Myers (Ocean Modelling, 2025)

Debunking common myths in coastal circulation modeling - Y. Joseph Zhang; Joshua Anderson; Kyungmin Park; Chin H. Wu; Spenser Wipperfurth; Eric Anderson; Shachak Pe'eri; Dmitry Beletsky; Daniel Titze; Emanuele Di Lorenzo; Saeed Moghimi; Gregory Seroka; et al. (Ocean Modelling, 2024)

Simulating flood events at the Twin Ports of Duluth-Superior using a linked hydrologic-hydrodynamic framework - Lindsay Fitzpatrick; Daniel Titze; Eric J. Anderson; Dmitry Beletsky; John G. W. Kelley (Ocean Dynamics, 2023)
Generally, ports in the North American Great Lakes are not supported with navigational guidance (water level, water temperature, currents, ice) by NOAA’s Great Lakes Operational Forecast System (GLOFS). To examine the benefit of extending model coverage to this critical infrastructure, a linked hydrologic-hydrodynamic framework was developed for the Twin Ports of Duluth-Superior in western Lake Superior, and tested over three case studies of flooding due to storm surge and/or river flooding. Streamflow from 22 National Water Model (NWM) simulated and 3 gauged inflows within the domain was injected into a hydrodynamic model built on the Finite Volume Community Ocean Model (FVCOM), with a wet-dry grid that covered the harbor and surrounding floodplain. Model results from flood simulations compared well against time-series of water level and streamflow at gauges within the harbor, with root mean square error (RMSE) and bias values small relative to the typical fluctuations. Inclusion of NWM-simulated tributaries improved the accuracy of modeled water levels in the harbor, and increased simulated current speeds in navigational channels by up to 0.5 ms −1 . Modeled inundation extent in the floodplain closely matched flood extent surveys conducted in response to a record flood event in 2012, demonstrating the capability of the modeling framework to provide flood guidance in the complex coastal setting.

Development and skill assessment of a real-time hydrologic-hydrodynamic-wave modeling system for Lake Champlain flood forecasting - Daniel Titze; Dmitry Beletsky; Jesse Feyen; William Saunders; Lacey Mason; James Kessler; Philip Chu; Deborah Lee (Ocean Dynamics, 2023)

Reclassification of Sphaerotilus natans subsp. sulfidivorans Gridneva et al. 2011 as Sphaerotilus sulfidivorans sp. nov. and comparative genome analysis of the genus Sphaerotilus - Margarita Y. Grabovich; Dmitry D. Smolyakov; Alexey V. Beletsky; Andrey V. Mardanov; Maria V. Gureeva; Nikita D. Markov; Tatyana S. Rudenko; Nikolai V. Ravin (Archives of Microbiology, 2021)

Modeling the ice-attenuated waves in the Great Lakes - Peng Bai; Jia Wang; Philip Chu; Nathan Hawley; Ayumi Fujisaki-Manome; James Kessler; Brent M. Lofgren; Dmitry Beletsky; Eric J. Anderson; Yaru Li (Ocean Dynamics, 2020)

A sensitive environmental DNA (eDNA) assay leads to new insights on Ruffe (Gymnocephalus cernua) spread in North America - Andrew J. Tucker; W. Lindsay Chadderton; Christopher L. Jerde; Mark A. Renshaw; Karen Uy; Crysta Gantz; Andrew R. Mahon; Anjanette Bowen; Timothy Strakosh; Jonathan M. Bossenbroek; Jennifer L. Sieracki; Dmitry Beletsky; et al. (Biological Invasions, 2016)